Triticum aestivum L. group aestivum CGN08869 ... - GLIS Of The ITPGRFA (Centre for Genetic Resources, the Netherlands, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. group aestivum Common name(s): wheat Other names: Tundra Conserved by: Centre for Genetic Resources, the Netherlands (CGN), Netherlands (Kingdom of the) Local sample unique identifier: CGN08869 Method of creation: Acquisition Date: 1988-09-24 Other identifiers: purl,http://purl.org/cgngenis/accenumb/CGN08869 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...